Speaker recognition system - Song, Liyan. (2012)
This report givens an overview of a Gaussian Mixture Model – Universal Background Model (GMM-UBM) system which focusing on speaker identification. In this report we will be focusing on the traditional FFT-based Mel-Frequency Cepstral Coefficients (MFCCs) method to extract feature from wav file and GMM-UBM to create speaker model. The detail information of MFCC and GMM-UBM will be explained in the report.